An asymmetrical model for high-energy radiation of Cassiopeia A. Issue 2 (5th May 2022) - Zhan, Shihong; Wang, Wei; Mou, Guobin; Li, Zhuo
ABSTRACT: The supernova remnant Cassiopeia A (Cas A) shows strong radiation from radio to gamma-ray bands. The mechanism of gamma-ray radiation in Cas A and its possible contribution to PeV cosmic rays are still under debate. The X-ray imaging reveals an asymmetric profile of Cas A, suggesting the existence of a jet-like structure. In this paper, we propose an asymmetrical model for Cas A, consisting of a fast moving jet-like structure and a slowly expanding isotropic shell. This model can account for the multiwavelength spectra of Cas A, especially for the power-law hard X-ray spectrum from ∼60 to 220 keV. The GeV to TeV emission from Cas A should be contributed by both hadronic and leptonic processes. Moreover, the jet-like structure may produce a gamma-ray flux of 10^-13erg cm^-2 s^-1 at ∼100 TeV, to be examined by the Large High Altitude Air Shower Observatory (LHAASO) and the Cherenkov Telescope Array (CTA).